Surya Namaskar Yoga and Chamomile Essential Oil Aromatherapy on Hot Flashes and Insomnia in Perimenopausal Women - Handayani; Levi Tina Sari; Ita Noviasari (Journal of Ners and Midwifery, 2025)
As women approach perimenopause, aging of the ovaries causes a decrease in estrogen production. The inability to maintain adequate estrogen levels, whether due to low production or other factors, can cause a variety of physical and psychological changes, including irregular periods, hot flashes, and insomnia. The purpose of this study was to find the effectiveness of Surya Namaskar Yoga and Chamomile Essential Oil Aromatherapy on Hot Flashes and Insomnia in Perimenopausal Women. This was a quasi-experimental study with a control group design. The sample size of this study used the Slovin formula to obtain 80 respondents. Bivariate data using the Kolmogorov Smirnov test, if the data is normally distributed then using the paired sample t-test, and to compare between the control group and the treatment group using the ANOVA test. The results for comparing the control and treatment groups obtained p = 0.031, which means that there was a significant difference in the post-test value of insomnia complaints between the control and treatment groups, and p 0.041 < α 0.05. P 0.007 < α 0.005, meaning there was a significant difference in the post-hot Flashes complaint value between the control and treatment groups. The combination of Suryanamaskar yoga and chamomile aromatherapy provides a synergistic effect in improving insomnia and hot Flashes. It is expected that yoga and chamomile aroma therapy can be used to perimenopausal women so that they can prevent the uncontrollable perimenopause syndrome.